GHR is involved in gastric cell growth and apoptosis via PI3K/AKT signalling. Issue 5 (25th January 2021) - Yan, Hong‐Zhu; Wang, Hua‐Feng; Yin, Yueling; Zou, Jue; Xiao, Feng; Yi, Li‐Na; He, Ying; He, Bo‐Sheng
Abstract: Growth hormone receptor (GHR), the cognate receptor of growth hormone (GH), is a membrane bound receptor that belongs to the class I cytokine receptor superfamily. GH binding GHR induces cell differentiation and maturation, initiates the anabolism inside the cells and promotes cell proliferation. Recently, GHR has been reported to be associated with various types of cancer. However, the underlying mechanism of GHR in gastric cancer has not been defined. Our results showed that silence of GHR inhibited the growth of SGC‐7901 and MGC‐803 cells, and tumour development in mouse xenograft model. Flow cytometry showed that GHR knockout significantly stimulated gastric cancer cell apoptosis and caused G1 cell cycle arrest, which was also verified by Western blot that GHR deficiency induced the protein level of cleaved‐PARP, a valuable marker of apoptosis. In addition, GHR deficiency inhibited the activation of PI3K/AKT signalling pathway. On the basis of the results, that GHR regulates gastric cancer cell growth and apoptosis through controlling G1 cell cycle progression via mediating PI3K/AKT signalling pathway. These findings provide a novel understanding for the role of GHR in gastric cancer.